Addition of Chlorhexidine Gluconate to a Glass Ionomer Cement: A Study on Mechanical, Physical and Antibacterial Properties - Marti, Luana Mafra; Mata, Margareth Da; Ferraz-santos, Beatriz; Azevedo, Elcilaine Rizzato; Giro, Elisa Maria Aparecida; Zuanon, Angela Cristina Cilense (Fundação Odontológica de Ribeirão Preto, 2014)
The objective of this work was to determine the effect of different concentrations of chlorhexidine digluconate (CHX) on setting time, surface hardness, maximum tensile bond strength and antibacterial activity of a glass ionomer cement (GIC). The material used as control was Ketac Molar Easymix GIC. CHX was incorporated into the GIC during its manipulation at concentrations of 0.5, 1.0 and 2.0%. Antimicrobial activity against S. mutans and L. acidophilus was evaluated by means of agar diffusion test. Tensile bond strength data were analyzed statistically using Analysis of variance and Tukey's test. Setting time, Vickers hardness and agar diffusion test were analyzed using Kruskal-Wallis and Mann-Whitney tests at a significance level of 5%. It was observed that adding CHX at concentrations of 1% and 2% increased significantly the setting time of the material (p=0.012 and p=0.003, respectively). There was no significant difference between control and 0.5% CHX groups regarding the setting time. Addition of 2% CHX decreased significantly the surface hardness in relation to the control group (p=0.009), followed by the 1% CHX group (p=0.009). The tensile bond strength of the material also decreased significantly after adding CHX at a concentration of 2% (p=0.001). Addition of CHX promoted formation of an inhibition halo in both bacterial strains for all concentrations. The results showed that the best option for clinical use of GIC with CHX is at 0.5% concentration, since antibacterial activity increased and the physical-mechanical properties remained unchanged.

O objetivo deste trabalho foi determinar o efeito de diferentes concentrações de gluconato de clorexidina (CLX) sobre o tempo de presa, dureza superficial, resistência máxima a tração e atividade antibacteriana de um cimento de ionômero de vidro (CIV). O material utilizado como controle foi o CIV Ketac Molar Easymix. O gluconato de CHX foi incorporado no CIV durante a sua manipulação, em concentrações de 0,5, 1,0 e 2,0%. Atividade antimicrobiana contra S. mutans e L. acidophilus foi avaliada por meio de teste de difusão em ágar. Análise de variância (ANOVA) e teste de Tukey foram usadas para avaliar a resistência a tração do material. Para avaliar tempo de presa, dureza Vickers e teste de difusão em ágar foram usados os testes de Mann-Whitney e Kruskal-Wallis ao nível de significância de 5%. Observou-se que a adição de CHX, em concentrações de 1% e 2%, aumentou significativamente o tempo de presa do material (p = 0,012 e p = 0,003, respectivamente). Não houve diferença significativa entre os grupos controle e CHX 0,5% em relação ao tempo de presa. A adição de 2% de CHX diminuiu significativamente a dureza superficial, em relação ao grupo controle (p = 0,009), seguido pelo grupo 1% de CHX (p = 0,009). A resistência à tração do material também diminuiu significativamente após a adição de CHX a uma concentração de 2% (p = 0,001). A adição de CHX promoveu formação de halo de inibição em ambas as linhagens bacterianas para todas as concentrações. Os resultados mostraram que a melhor opção para o uso clínico de CIV com CHX está numa concentração de 0,5%, uma vez que a atividade antibacteriana aumentada e as propriedades físico-mecânicas permaneceram inalteradas.
Keywords: glass-ionomer cement; chlorhexidine; compressive strength